‘Classicon’: Innovative Design from Classical and Contemporary African Textile Print Design Concepts - Isaac Abraham; Charles Frimpong; Ebenezer Kofi Howard (ITB Journal Publisher, LPPM ITB, 2018)
Wax prints were the earliest textile prints exported to Ghana by the Europeans. These prints, commonly referred to as African prints, have distinguishing characteristics, with the earlier ones, known as classical prints, exhibiting symbolic patterns largely used by Ghanaians in the 19th and the 20th century. With the newer trends of fashion in the 21st century, the design preference in these special textiles changed from complex symbolic patterns to simple stylized patterns and textile producers adopted more creative ways in designing to satisfy the taste and demands of textile consumers. The purpose of the present practice-based research was to widen the scope of African print designs by creating new designs that incorporate classical and contemporary design concepts. Samples of African prints were observed and the findings led to the development of new designs christened ‘Classicon’. These prints, based on the transitional design approach (TDA), combine the elements, principles and philosophy of both the classical and contemporary designs to create a class of designs that bridge the gap between the two concepts. This study recommends Classicon prints to Afro-centric designers not only to preserve African ethnic patterns but also to update African classical prints to suit current fashion trends.